Controlling local order of athermal self-propelled particles. (5th December 2016) - Dougan, Niamh; Crowther, Peter; Patrick Royall, C; Turci, Francesco
Abstract: We consider a model of self-propelled dynamics for athermal active particles, where the non-equilibrium active forces are modelled by a Ornstein–Uhlenbeck process. In the limit of no-driving force, the model reduces to the passive, Brownian dynamics of an atomistic glass forming fluid, the Wahnström binary mixture. The Wahnström mixture is known to show strong correlations between the emergence of slow dynamics and the formation of locally favoured structures based on icosahedra. Here, we study how the non-equilibrium driving affects the local structure of the system, and find that it strongly promotes icosahedral order. The states rich in local icosahedral order correspond to configurations of very low potential energy, suggesting that the non-equilibrium dynamics in the self propelled model can be effectively exploited to explore the potential energy surface of the binary mixture and have access to states that are difficult to attain using passive dynamics.